ANALYSIS OF THE EFFECT OF CREDIT GROWTH, NPL, CREDIT RESTRUCTURING AND CREDIT WRITE-OFF ON STOCK PRICES WITH PROFITABILITY AS AN INTERVENING VARIABLE - Darno Setiawan B Zendrato; Erlina; Khaira Amalia Fakhrudin (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2025)
This study aims to analyze the effect of credit growth, non-performing loans (NPLs), credit restructuring, and loan write-offs on stock prices, with profitability as an intervening variable. The companies studied are banking companies listed on the Indonesia Stock Exchange. Credit policy and management are crucial elements in the banking industry, as they serve not only as banks but also as the company's primary source of revenue. This study employed a quantitative approach with multiple linear regression. Data management and analysis were performed using Eviews version 12. The sample consisted of 37 banking companies selected purposively over a three-year observation period (2022-2024), resulting in a total of 111 observations. The analysis showed that credit growth had a positive and significant effect on stock prices, while non-performing loans (NPLs) and loan restructuring had a negative and significant effect on stock prices. While loan write-offs had no effect on stock prices, credit growth had no effect on stock prices. Credit growth has a negative and significant effect on stock prices with profitability as an intervening variable, conversely NPL and credit restructuring have a positive and significant effect on stock prices with profitability as an intervening variable while credit write-offs have no effect on stock prices with profitability as an intervening variable.